Pengaruh Pemberian Pupuk Organik Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max (L.) Merril) - Nurlisan '; Aslim Rasyad; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was intended to determine the possibility of manure application to replace inorganig fertilizer on crop growth and seed yield of soybean. A field experiment was conducted at the experimental farm of the Faculty of Agriculture University of Riau, Pekanbaru in 2013. The experiment was arranged in randomized block designwith seven treatments and three replications. The treatments were recommended rate of inorganic fertilizers (Urea 55 kg/hectare, TSP 55 kg/hectare and KCl 73 kg/hectare), chicken manure at rates of 2 tons, 3 tons and 4 tons per hectare; cow manure at rates of 10 tons, 12 tons and 14 tones per hectare. Seed of G19BE genotype was planted in a plot of 3m x 2 m with the planting space of 40 cm x 20 cm. All rates of animal manure were apllied 10 days before planting while fertilizer was applied at planting date. The results showed that inorganic fertilizer and any kinds of manure affected vegetative growth of soybean at the same manners. Application of cow and chiken manure, in general, yielded more filled pods, more number of seeds per plant, seed weight per plant and seed yield m -2 than inorganic fertilizer application. Chicken manure ate of 4 ton hectare yielded greater seed weight per m² compared to cow manure or artificial fertilizer. This result suggests that organic manure may be utilized to replace inorganic fertilizer in soybean cultivation. Keywords: Chicken manure, cow manure, soybean